Ozonioterapia: regulamentação jurídica - (:unkn) unknown (Universidade Brasil, 2020)
The present work aims to address the use of ozone therapy for treatment in humans, combined with the need to provide specific and complete legal guidelines. Ozone is a highly toxic gas, but it has an important antioxidant, bactericidal, anti-inflammatory characteristic and helps in the repair process. For this reason, the artificial production of this gas was started, for its therapeutic use, whose technique is called ozonotherapy. However, it is questioned whether the technique is a safe and effective treatment, since application in inadequate doses or routes of application can bring serious results to the patient. Currently, when the chosen route is auto-hemotherapy, it is possible that it is administered in a judicious and personal way, making the analysis of the individual's biomarkers and their tolerance to ozone, given the fact that the levels of gas tolerance are different in each subject. It turns out that, there is no specific legislation that ensures which professionals can prescribe and use ozone therapy, having several class councils already positioned themselves favorably. In 2018, the Ministry of Health incorporated ozone therapy as an integrative and complementary practice of the Unified Health System, provided it is applied in precise therapeutic doses, without, however, establishing criteria for the definition of the dose to be applied. Health is a social right that must be safeguarded in order to preserve a healthy and dignified life, which is why any health treatment can only be prescribed and carried out under appropriate conditions of safety and inspection, supported by scientific research and its own legislation. It is necessary to have specific and complete legislation on the subject, able to bring parameters and application protocols, in order to provide guarantees to professionals and patients who intend to treat. Thus, a research of the literature was carried out on electronic bases in the health and legal areas, there was no restriction on languages or publication data. Several articles were found, eliminating a duplication of titles and after reading abstracts, selected those that best fit the theme of this work. In a next step, perform a complete reading of all articles and the theoretical framework of this thesis was created. After reading and selecting the few and incomplete regulations on ozone therapy, he made a published work, which is a proposal for a complete review of the legislative content on ozone therapy. The proposed regulation brings the main parameters for the application of the technique, as well as the contraindicated routes, training of the professional who will manage the therapy, the qualified professionals, cautionary exams when due to auto-hemotherapy, care and responsibilities. In this sense, the present proposal of legislative content, was delivered to members of the Legislative Power, so that, observing the constitutional requirements, it can be used as a basis for the project, and eventually a future law, which will contain adequate and complete content regarding the theme.
Keywords: Ozônio; Aplicação; Legislação - saúde; Engenharia Biomédica (Bioengenharia)